Academic solidarity in the time of genocide - Vivienne Badaan (12525976) (2025)
In this paper, we engage with the manifestations of academic solidarity with Palestine, particularly those that have appeared since October 2023. We problematise the prevalence of performative and conditional support that criminalises resistance to the occupation and requires Palestinians to be passive victims. We analyse a three-tiered framework of solidarity in academic spaces: Macro-level institutional repression, Meso-level faculty conditional solidarity which preserves privilege, and Micro-level student-led unconditional solidarity despite high precarity. Drawing on participatory observations, student activist interviews and systematic databasing of solidarity initiatives, we analyse academic solidarity models and backlash in the United States, United Kingdom and Lebanon. We argue that unconditional solidarity with Palestinian liberation requires a rupture from virtue signaling, which necessitates a greater willingness to take risks and a commitment to the frameworks advanced by Palestinian academics and collectives. We conclude by advocating for an unconditional solidarity model, as defined by Palestinian scholars, that centres liberation, rematriation and return over humanitarianised victimhood. Other Information Published in: Globalisation, Societies and Education License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1080/14767724.2025.2558989